ORANG TUA SEBAGAI MOTIVASI TUMBUH DAN BERKEMBANGNYA ANAK DALAM PEMBENTUK SIKAP DAN KARAKTER - Hutabarat, Dany Try Hutama; Sinambela, Nur Isnaini; Lubis, Lili Khairani Azhari; Siagian, Zairul Abdi; Alkarim, Fazri; Ananta, Aulia; Azura, Putri; Siregar, Sahmul Ruhum; Rizki, Muhammad Muhajir; Maimunah, Intan (Nusantara Hasana Berdikari, 2022)
Based on the development of a good thought from a child, it must start with parental support, there are also other supporting factors such as the environment, relatives, friends, and teachers. parents and children in order to reduce disputes about child crimes, delinquency of a child and take a step further to encourage them to form good attitudes and character for the children of the Indonesian nation. children will make children better in terms of interacting, learning, free without pressure. There are many children who do not know the identity and genealogy of their families whose children do inappropriate things such as stealing, begging, and do other things that can disturb other audiences.